Flow battery based on recycled lithium ions to stabilize high-concentration iron electrolyte

By using the combination of waste lithium-ion battery positive electrode material and deliquency catalyst in the liquid flow battery, the lithium element is extracted and the solubility of ferrocyanone is improved, and the problems of high recycling costs and low battery energy density are solved, achieving high efficiency and low Cost lithium ion recovery and battery performance improvements.

CN118693319BActive Publication Date: 2024-12-20CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411158318.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-20
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

In the prior art, the recycling cost of waste lithium-ion battery positive electrode materials is high, the environmental pollution is serious, and the low solubility of ferrocyanium in the iron-based electrolyte leads to low battery energy density.

Method used

Design a liquid flow battery based on the recycling of lithium ions and stable high concentration ferrolyte solution. By combining the positive electrode material of waste lithium ion battery with deliquency catalyst, lithium elements are extracted, the stability of iron-based electrolyte solution is improved, and the heteroionic effect is achieved. Improve the solubility of ferrocyanium and achieve high selective recycling and reuse.

Benefits of technology

It greatly reduces the cost and time of recycling the positive electrode material of waste lithium-ion batteries, extends the life and energy density of iron-based flow batteries, reduces the cost of batteries, and is suitable for large-scale industrial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118693319B_ABST
    Figure CN118693319B_ABST
Patent Text Reader

Abstract

The present invention discloses a flow battery based on recycling lithium ion stable high concentration iron electrolyte, including a positive electrode storage tank and a negative electrode storage tank, wherein the positive electrode storage tank stores positive electrode electrolyte, wherein the positive electrode electrolyte stores a de-lithiation catalyst, waste lithium ion battery positive electrode material and a filtering device; wherein the negative electrode storage tank stores negative electrode electrolyte; further comprising a positive electrode half-cell and a negative electrode half-cell, wherein the positive electrode half-cell and the negative electrode half-cell are separated by a diaphragm; wherein the positive electrode storage tank and the positive electrode half-cell are cyclically connected through a transmission pipeline, and the negative electrode storage tank and the negative electrode half-cell are cyclically connected through another transmission pipeline; and a circulation pump is provided on both transmission pipelines. The present invention solves the problems of high recycling cost, environmental pollution, difficulty in recycling and reuse of waste lithium ion battery positive electrode materials, and low solubility of ferrocyanide as an active substance in iron-based electrolytes, resulting in low battery energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries and relates to a liquid flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte. Background Art

[0002] With the continuous exploitation of fossil energy and the increasing environmental pollution problems, countries have increased the development and utilization of clean energy such as solar energy, wind energy, tidal energy and geothermal energy. However, these clean energy sources are difficult to connect to the grid due to their discontinuity and instability. Therefore, large-scale energy storage devices are needed to smooth their peaks and valleys and promote their grid connection. Liquid flow batteries have become one of the most promising ideal candidates for large-scale energy storage technology due to their advantages of capacity and power decoupling, long cycle life and high safety. However, the most mature commercial all-vanadium liquid flow batteries have the disadvantages of severe strong acid corrosion, low energy efficiency and high price. These problems have greatly hindered the large-scale development and commercialization of redox liquid flow batteries. Ferrocyanide / ferrocyanide has been widely used in various liquid flow battery systems and has been widely studied due to its abundant reserves, good stability, high electrochemical reversibility and low chemical cost. However, the solubility of potassium ferrocyanide and sodium ferrocyanide in water is only 0.76 M and 0.56 M. In order to improve the solubility of ferrocyanide, since 2017, Professor Jia Chuankun of Changsha University of Science and Technology has mixed potassium ferrocyanide and sodium ferrocyanide based on the isocyanate effect, gradually increasing the solubility of ferrocyanide from 0.76 M / 0.56 M to 1.46 M and 1.52 M under alkaline conditions. They were applied to alkaline zinc-iron flow batteries and alkaline iron-sulfur flow batteries, respectively, greatly improving the solubility of the positive electrode active material.

[0003] At the same time, lithium-ion batteries are widely used in consumer electronics, electric vehicles, energy storage and other fields due to their excellent electrochemical properties. However, the life of lithium-ion batteries is 3 to 10 years, and the retirement of lithium-ion batteries has arrived. Waste lithium-ion batteries not only contain a large number of recyclable metal elements, but also contain toxic electrolytes and heavy metals. Discarding them at will not only pollutes the environment, but also causes a large amount of resource waste. The current recycling methods include pyrometallurgical recycling and wet recycling. Pyrometallurgical recycling has problems such as low metal recovery rate, high equipment requirements, further refining of metals, and the generation of toxic and harmful gases. Wet recycling uses acids, alkalis and microorganisms to leach metals from waste lithium-ion batteries to obtain soluble salts or precipitates, but it has the disadvantages of low leaching efficiency, long leaching time and relatively high cost.

[0004] The invention patent with the publication number CN114084877A discloses a method for obtaining ultrapure iron phosphate from waste lithium iron phosphate pole piece materials and the obtained ultrapure iron phosphate, wherein the pretreated waste lithium iron phosphate pole piece materials are placed in a mesh bag; a flow battery is constructed, and a redox couple with a potential higher than or equal to that of lithium iron phosphate is used as an active substance in the positive electrode electrolyte; after a charge and discharge cycle, the waste lithium iron phosphate pole piece materials are taken out, and ultrapure iron phosphate is obtained by washing and drying. However, on the one hand, it only recycles waste lithium iron phosphate to obtain iron phosphate, and does not involve the application of lithium ions and the recovery of other waste lithium ion battery positive electrode materials, and the performance of the flow battery constructed in the patent is poor; on the other hand, the oxidation state of ferrocyanide or ferrocyanide exists as one of its optional active substances, which only plays a role in delithiation, but is not a necessary element in the composition of the positive electrode electrolyte of the flow battery. According to its records, the active material only uses one of the active materials disclosed by it. If the oxidation state of ferrocyanide or ferrocyanide is selected to remove lithium from waste lithium iron phosphate, there is no need to use other active materials. At the same time, the solubility of the iron electrolyte composed of ferrocyanide ions in water is too low, which will greatly reduce the performance of the liquid flow battery formed. Summary of the invention

[0005] To achieve the above objectives, the present invention provides a flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte, which solves the problems of high recycling cost, environmental pollution, difficulty in recycling and reuse of waste lithium-ion battery positive electrode materials, and low solubility of ferrocyanide as an active substance in the iron-based electrolyte, resulting in low battery energy density.

[0006] The technical solution adopted by the present invention is a flow battery based on recycling lithium ion-stabilized high-concentration iron electrolyte, comprising a positive electrode storage tank and a negative electrode storage tank, wherein the positive electrode storage tank stores a positive electrode electrolyte, wherein a de-lithium catalyst, waste lithium ion battery positive electrode material and a filter device are stored in the positive electrode electrolyte; and the negative electrode storage tank stores a negative electrode electrolyte;

[0007] It also includes a positive electrode half-cell and a negative electrode half-cell, and the positive electrode half-cell and the negative electrode half-cell are separated by a diaphragm; the positive electrode liquid storage tank and the positive electrode half-cell are circulated and connected through a transmission pipeline, and the negative electrode liquid storage tank and the negative electrode half-cell are circulated and connected through another transmission pipeline; and a circulation pump is provided on both transmission pipelines;

[0008] The preparation method of the positive electrode electrolyte comprises: dissolving ferrocyanide or an oxidized state of ferrocyanide in water to obtain a positive electrode active substance, adding a delithiation catalyst and a positive electrode supporting electrolyte, and fully stirring and dissolving to obtain a positive electrode electrolyte;

[0009] The preparation method of the delithiation catalyst comprises: dissolving one or more of vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium oxychlorate, ferrocene and ferrocene derivatives, nitrogen oxides, hydroquinone and hydroquinone derivatives in an aqueous solution to prepare a delithiation catalyst; the material potential of the delithiation catalyst is higher than that of the positive electrode material of the waste lithium ion battery;

[0010] The concentration of the positive electrode active material is 0.1-1.74M; the concentration of the delithiation catalyst is 0.1-4.0M; and the concentration of the positive electrode supporting electrolyte is 0.1-4.0M.

[0011] Furthermore, the ferrocyanide includes one or more of potassium ferrocyanide, sodium ferrocyanide, ammonium ferrocyanide, lithium ferrocyanide, Prussian blue, and Prussian white; the oxidation state of the ferrocyanide includes one or more of potassium ferrocyanide, sodium ferrocyanide, and lithium ferrocyanide.

[0012] Furthermore, the positive electrode supporting electrolyte is a mixture of one or more solutions of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid.

[0013] Furthermore, the filtering device is any one of polyester filter cloth, polypropylene filter cloth, nylon filter cloth, vinylon filter cloth, polyethersulfone filter membrane, graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphene-modified carbon felt, graphyne-modified carbon felt, nickel mesh, modified nickel mesh, biomass-modified electrode, sulfide-modified electrode, bismuth-modified electrode, carbon nanotube composite electrode, and silicon oxide-modified electrode; the filtering device is used to prevent waste lithium-ion battery positive electrode materials from entering the positive electrode half-cell or transmission pipeline.

[0014] Furthermore, the preparation method of the diaphragm is:

[0015] When using K + 、Na + , Li + or NH4 + When ions are used as positive and negative electrode conducting ions, the diaphragm is placed in an alkaline solution having corresponding positive and negative electrode conducting ions selected from the group consisting of LiOH, NaOH, KOH, NH3·H2O, NH4 HCO3, (NH4)2CO3, Li2CO3, Li2HCO3, Na2CO3, NaHCO3, K2CO3, KHCO3, Li2O, Na2O or K2O, and the diaphragm is subjected to constant temperature treatment at a temperature of 25°C to 80°C for 1.5h to 12h. After the constant temperature heating treatment, the diaphragm is repeatedly washed with deionized water until the pH value of the deionized water is 6 to 7, and K + 、Na+ , Li + or NH4 + Type ion exchange membrane;

[0016] When using H + When used as positive and negative electrode ion conductors, the diaphragm is treated with hydrochloric acid or sulfuric acid before use to fill the diaphragm with H + , the membrane was repeatedly washed with deionized water until the pH of the deionized water was 6-7, and H + Type ion exchange membrane;

[0017] When anions are used as positive and negative electrode conductive ions, the diaphragm is soaked in a supporting electrolyte or a solution prepared with positive and negative electrode active materials before use, and then treated at a constant temperature. The diaphragm is then repeatedly washed with deionized water until the pH of the deionized water is 6~7, thereby obtaining an anionic ion exchange membrane.

[0018] Furthermore, the electrode of the positive half-cell and the electrode of the negative half-cell both use any one of graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphite plate, graphene-modified carbon felt, graphyne-modified carbon felt, nickel mesh, modified nickel mesh, activated carbon, carbon nanotubes, carbon aerogel, biomass-modified electrode, sulfide-modified electrode, bismuth-modified electrode, carbon nanotube composite electrode, and silicon oxide-modified electrode as the electrode material.

[0019] Furthermore, the preparation method of the negative electrode electrolyte is:

[0020] One or more of zinc-containing compounds, sulfides, iron-containing compounds, titanium-containing compounds, vanadium-containing compounds, quinone derivatives, phenazine derivatives, viologen derivatives, alloxazine derivatives, and fluorenone derivatives are dissolved in an aqueous solution, and then a negative electrode supporting electrolyte is added and fully stirred to dissolve.

[0021] Furthermore, the negative electrode supporting electrolyte is any one of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, or a mixture of multiple solutions.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention aims at the recycling and reuse of positive electrode materials of waste lithium-ion batteries, and proposes a liquid flow battery based on recycling lithium-ion stable high-concentration iron electrolyte. After simple treatment, the positive electrode of the waste lithium-ion battery is added to the iron-based electrolyte, and the lithium element in the waste lithium-ion battery is extracted using a delithiation catalyst. With the addition of lithium element, the stability of the iron-based electrolyte can be improved, and high selectivity of lithium element is achieved, which greatly reduces the cost and time of recycling positive electrode materials of waste lithium-ion batteries, and effectively solves the problems of high recycling cost, great environmental harm and difficulty in recycling and reuse of positive electrode materials of lithium-ion batteries.

[0024] 2. The lithium element recovered by the present invention improves the stability of the active material in the iron-based electrolyte in the solution, and at the same time increases the concentration of the positive electrode active material to a maximum of 1.74 M, and the constructed high-concentration iron-based electrolyte can work normally in a wide temperature range of -20°C to 60°C. The life of the iron-based liquid flow battery and the energy density of the battery are greatly extended, while further reducing the cost of the iron-based liquid flow battery.

[0025] 3. The liquid flow battery of the present invention has the industrial practical characteristics of easy-to-obtain raw materials, low cost, simple preparation process, simple and easy operation, and low-cost equipment, and is suitable for large-scale industrial development.

[0026] In summary, the present invention achieves high selection, high recovery rate and high reuse rate of lithium elements by adding the waste lithium-ion battery positive electrode material after simple treatment into the iron-based electrolyte of the iron-based liquid flow battery. Moreover, with the addition of lithium elements, the stability of the iron-based electrolyte is further improved, which greatly prolongs the stability of the iron-based liquid flow battery and further reduces the cost of the iron-based liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 It is a schematic structural diagram of a flow battery based on recycling lithium ions to stabilize a high-concentration iron electrolyte according to the present invention.

[0029] Figure 2 This is a comparison of the binding energy between ferrocyanide and other components under different supporting electrolytes.

[0030] Figure 3 This is a graph showing the energy density change when the solubility of the positive electrode solution increases to 1.74 M after adding lithium ions.

[0031] Figure 4 This is a comparison chart of the long-term stability of high-concentration positive electrode solutions after adding lithium ions.

[0032] Figure 5 It is a potential comparison diagram of different waste lithium-ion battery positive electrode materials and delithiation catalysts in the embodiments of the present invention.

[0033] Figure 6 This is a cycle performance diagram of the zinc-iron flow battery with waste lithium iron phosphate added in Example 1 of the present invention.

[0034] Figure 7 Schematic diagram of the extraction rate of lithium element in the positive electrode solution with cycle time in Example 1 of the present invention.

[0035] Figure 8 This is a cycle performance diagram of the zinc-iron liquid flow battery in Example 2 of the present invention with waste lithium iron phosphate added at an ambient temperature of -20°C.

[0036] Fig. 9 It is a cycle performance diagram of the zinc-iron liquid flow battery with waste lithium iron phosphate added at different ambient temperatures in Example 3 of the present invention.

[0037] Fig.10 This is a cycle performance diagram of the zinc-iron liquid flow battery in Example 4 of the present invention with waste lithium iron phosphate added at an ambient temperature of 60°C.

[0038] Fig.11 This is a cycle performance diagram of the zinc-iron liquid flow battery with 1.74 M positive electrode active material in Example 5 of the present invention.

[0039] Fig.12 This is a comparison chart of the volume capacity of the 1.74 M cathode solution and the 1.00 M cathode solution in Example 5 of the present invention.

[0040] Fig.13 It is the cyclic voltammetry curve of 4-OH-TEMPO in Example 6 of the present invention.

[0041] Fig.14 This is a cycle performance diagram of the zinc-iron liquid flow battery with waste lithium cobalt oxide added in Example 6 of the present invention.

[0042] Fig.15 This is a cycle performance diagram of the zinc-iron liquid flow battery with waste lithium manganese oxide added in Example 7 of the present invention.

[0043] Fig.16 This is a cycle performance diagram of the zinc-iron liquid flow battery with waste nickel cobalt manganese oxide added in Example 8 of the present invention.

[0044] Fig.17 This is a cycle performance diagram of the zinc-iron liquid flow battery with waste nickel cobalt aluminum oxide added in Example 9 of the present invention.

[0045] Fig.18 This is a rate performance diagram of the zinc-iron liquid flow battery with waste lithium iron phosphate added in Example 1 of the present invention.

[0046] Fig.19 This is a cycle performance diagram of the iron-sulfur liquid flow battery in Example 10 of the present invention.

[0047] Fig. 20 This is a cycle performance diagram of the iron-iron liquid flow battery in Example 11 of the present invention.

[0048] Fig.21 This is a cycle performance diagram of the iron-titanium liquid flow battery in Example 12 of the present invention.

[0049] Fig. 22 This is a cycle performance diagram of the iron-vanadium liquid flow battery in Example 13 of the present invention.

[0050] Fig.23 This is a cycle performance diagram of the iron-organic quinone flow battery in Example 14 of the present invention.

[0051] Fig.24 This is a cycle performance diagram of the iron-organic phenazine flow battery in Example 15 of the present invention.

[0052] Fig.25 This is a cycle performance diagram of the iron-organic viologen flow battery in Example 16 of the present invention.

[0053] Fig.26 This is a cycle performance diagram of the iron-organofluorenone type liquid flow battery in Example 17 of the present invention.

[0054] Fig. 27 This is a cycle performance diagram of the iron-organoalloxazine type liquid flow battery in Example 18 of the present invention.

[0055] Fig.28 This is a cycle performance diagram of the zinc-iron liquid flow battery in Comparative Example 1 of the present invention without adding waste lithium-ion battery positive electrode material.

[0056] Fig.29 This is a cycle performance diagram of the zinc-iron flow battery in which 0.5 g of waste lithium iron phosphate is added in Comparative Example 2 of the present invention.

[0057] Fig.30 This is a cycle performance diagram of the zinc-iron liquid flow battery in Comparative Example 3 of the present invention at -20°C without adding waste lithium-ion battery positive electrode material.

[0058] Fig.31 This is a physical picture of the positive electrode of the zinc-iron liquid flow battery in Comparative Example 3 of the present invention at -20°C without adding waste lithium-ion battery positive electrode material. DETAILED DESCRIPTION

[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] In view of the problems of high recycling cost, environmental pollution, difficulty in recycling and reuse of waste lithium-ion battery positive electrode materials, and low solubility of ferrocyanide as an active substance in iron-based electrolyte, which leads to low battery energy density, the present invention designs a liquid flow battery to extract lithium elements from waste lithium-ion battery positive electrode materials, thereby realizing green and efficient recycling of waste lithium-ion battery positive electrodes. After the lithium element enters the high-potential electrolyte, it enters the positive electrode electrolyte to complex with the positive electrode active substance, thereby improving the stability of the iron positive electrode electrolyte, greatly reducing the binding energy of the iron positive electrode electrolyte, and greatly improving the stability of the liquid flow battery. At the same time, based on the heteroion effect, the lithium ion proposed improves the solubility of ferrocyanide, and it can be increased to 1.74 M under the action of lithium ions. The assembled liquid flow battery can work stably and cyclically for a long time. See Figure 3 and Figure 4 The iron-based electrolyte constructed at the same time has a wide operating temperature range, and the normal operating range is from -20°C to 60°C. The embodiment of the present invention studies the mechanism of action of lithium ions on the stability of ferrocyanide for the first time, and at the same time realizes the green recycling of waste lithium-ion battery positive electrodes, completing the green recycling of lithium ions.

[0061] Specifically, Figure 2 As shown in Figure 2, under the action of lithium ions, the binding energy between ferrocyanide and other components is even lower, only -45.12 kJ mol -1 , which is much lower than the binding energy of the cathode solution without lithium ions (-32.51 kJ mol -1 ), and lower binding energy means that the ferrocyanide in the solution is more tightly bound to other components, and the stability of the system is better.

[0062] See also Figure 1 The basic components of the flow battery based on the recycling of lithium ion stable high-concentration iron electrolyte provided by the embodiment of the present invention include: positive and negative electrode storage tanks (a filter device is assembled in the positive electrode storage tank), waste lithium ion battery positive electrode materials, positive electrode half-cells, negative electrode half-cells, diaphragms, circulation pumps and corresponding transmission pipelines; wherein, the positive and negative electrode electrolytes are stored in the positive and negative electrode storage tanks respectively, the waste lithium ion battery positive electrode materials are stored in the positive electrode storage tank, the delithiation catalyst is stored in the positive electrode electrolyte, and the positive and negative electrode half-cells are composed of electrodes, tabs and sealing materials; when the battery is running, the electrolyte enters the positive and negative electrode half-cells through the externally connected transmission pipelines with the circulation of the circulation pump to carry out electrochemical reactions, and the positive and negative electrode half-cells are isolated by the diaphragm, which plays the role of ion transmission. The positive and negative electrode half-cell tabs are respectively connected to the positive and negative electrodes of the external power supply to provide electrical energy for the external power supply.

[0063] The preparation of the flow battery based on recycling lithium ions to stabilize the high-concentration iron electrolyte according to the embodiment of the present invention is specifically carried out according to the following steps:

[0064] Preparation of diaphragm: The main function of the diaphragm is to prevent the positive electrode, negative electrode and active material from direct contact, while selectively allowing designated ions to pass quickly to maintain the electrical neutrality of the electrolyte on both sides and form a current loop.

[0065] The diaphragms of the embodiments of the present invention are prepared by different methods depending on the types of conductive ions:

[0066] When using K + 、Na + , Li + or NH4 + When ions are used as positive and negative electrode conducting ions, the diaphragm is placed in an alkaline solution having corresponding ions selected from 0.1 M to 1 M LiOH, NaOH, KOH, NH3·H2O, NH4 HCO3, (NH4)2CO3, Li2CO3, Li2HCO3, Na2CO3, NaHCO3, K2CO3, KHCO3, Li2O, Na2O or K2O, and the diaphragm is subjected to constant temperature heating treatment, and the constant temperature treatment is carried out at a temperature of 25°C to 80°C for 1.5h to 12h, and the diaphragm is repeatedly washed with deionized water until the solution pH is 6 to 7, and K + 、Na + , Li + or NH4 + type ion exchange membrane, and then soaked in deionized water for use.

[0067] When using H + When used as positive and negative electrode ion conductors, the diaphragm is treated with hydrochloric acid or sulfuric acid before use to fill the diaphragm with H + The diaphragm includes: Nafion membrane, PP membrane, PE membrane, PEO membrane, SPEEK membrane, SPES membrane, PVDF membrane, PTFE membrane or PBI membrane, which can conduct H + The diaphragm can be repeatedly washed with deionized water until the pH of the deionized water is 6~7, and then soaked in deionized water for use.

[0068] When anions are used as positive and negative electrode conductive ions, the diaphragm needs to be soaked in a supporting electrolyte or a solution prepared with positive and negative electrode active materials before use, and treated at a constant temperature of 20℃~100℃ for 12~24 hours. The diaphragm is then repeatedly washed with deionized water until the pH of the deionized water is 6~7, and then soaked in deionized water for use.

[0069] Preparation of electrode materials: The main function of the electrode is to provide or accept the electrons required for the electrochemical reaction and serve as the place where the battery reaction occurs, providing active sites for the battery's redox reaction.

[0070] The positive and negative electrodes used in the present invention are all made of any one of graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphite plate, graphene-modified carbon felt, graphyne-modified carbon felt, nickel mesh, modified nickel mesh, activated carbon, carbon nanotubes, carbon aerogel, biomass-modified electrode, sulfide-modified electrode, bismuth-modified electrode, carbon nanotube composite electrode, and silicon oxide-modified electrode as electrode materials. Generally, the electrode material is a three-dimensional material, and its thickness is generally 3 to 8 mm. Within a certain range, the thicker the thickness, the more reactive sites there are on the electrode. However, when the thickness is too thick, the battery resistance will increase, affecting the battery electrochemical performance.

[0071] Preparation of negative electrode electrolyte: dissolve one or more of zinc-containing compounds, sulfides, iron-containing compounds, titanium-containing compounds, vanadium-containing compounds, quinone derivatives, phenazine derivatives, viologen derivatives, alloxazine derivatives, and fluorenone derivatives in an aqueous solution with a mass molar concentration of 0.1 M to 16 M; then add 0.1 M to 4.0 M of negative electrode supporting electrolyte, the negative electrode supporting electrolyte is any one of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, or a mixture of multiple solutions, and use a magnetic stirrer to fully stir and dissolve. The concentration of the negative electrode electrolyte must be selected to meet the requirements of providing the number of electrons required for the positive electrode reaction, while balancing the ionic strength of the positive electrode solution to prevent water migration. The selection of multiple negative electrode electrolytes in the present invention provides multiple directions for the development of recycling lithium elements from the positive electrode of waste lithium-ion batteries to improve the stability of liquid flow batteries.

[0072] Among them, the quinone derivatives are preferably selected from one or more of 2,6-dihydroxyanthraquinone (2,6-DHAQ), anthraquinone-2,6-disulfonate (AQDS), 9,10-anthraquinone-2,7-disulfonic acid diammonium salt (AQDS(NH4)2), 1,8-bis(2-(2-(2-(2-hydroxyethoxy)ethoxy)ethoxy)anthracene-9,10-dione (PEGAQ), and 2,2'-((9,10-dioxy-9,10-dihydroanthracene-2,6-diyl)bis(oxy))dipropionic acid (2,6-D2PEAQ).

[0073] Among them, the phenazine derivatives include one or more of phenazine (PZ), 2-hydroxyphenazine (PZ-OH), 1,2-dihydroxyphenazine (PZ-2OH), 7,8-dihydroxyphenazine-2-sulfonic acid (DHPS), 1,2-heptadecanoyl-SN-glycero-3-phosphocholine (DHPC), phenazine-(2,3-diyl)dioxydibutyric acid (DBEP), phenazine-(2,3-diyl)dioxydiacetic acid (DAEP), 2-hydroxyphenazine (HP), 2-amino-3-hydroxyphenazine (AHP), and benzohydroxyphenazine-7 / 8-carboxylic acid (BHPC).

[0074] Among them, the viologen derivatives are preferably viologen and its derivatives: viologen (MV), methyl viologen dichloride (MVCl2), 1,1'-dimethyl-4,4'-bipyridyl diiodide (MVI2), methyl viologen dibromide (MVBr2), 1-(1-oxo-2,2,6,6-tetramethylpiperidin-4-yl)-1'-(3-(trimethylamino)propyl)-4,4'-bipyridyl trichloride (((TPABPy)Cl3)PV 3+ )、BSP-Vi、BTMAP-Vi、BTMAE-Vi、1-methyl-1'-[3-(trimethylamino)propyl]-4,4'-trichlorobipyridinium ([(Me)(NPr)V]Cl3)、EDV-HBCD、1,1'-bis[3-(trimethylamino)propyl]-4,4'-tetrabromobipyridinium ([(NPr)2V]Br4)、1[3-(trimethylamino)propyl]1'(3-sulfonyl)4 , 4'-dipyridinium dibromide (((NPr)(SPr)V)Br2), 4,4'-(thiazole)thiazole-2,5-diyl)bis(1(3(trimethylammonium)propyl)pyridinium-1-ammonium) tetrachloride ([(NPr)2TTz]Cl4), 1,1'-bis(3-phosphonopropyl)-[4,4'-bipyridinium]-1,1'-dibromide disalt (BPP-Vi), bis(3-trimethylammonium-2-hydroxy)propyl viologen tetrachloride (Dex-Vi 4+ )

[0075] Among them, the oxazine derivatives are preferably selected from one or more of nicotinamide adenine dinucleotide (NAD), flavin mononucleotide (FMN), and riboflavin sodium phosphate (FMN-Na).

[0076] Among them, the fluorenone derivatives are preferably selected from one or more of 9-fluorenone (9-FL), 9-fluorenone-2-carboxylic acid (F2CA), 2-carboxylic acid-7-sulfonate fluorenone (4C7SFL), and 4-oxo-4,8,9,10-tetrahydro-7a,10a-diazacycloheptafluorene-7a,10a-dichloridum ((OTDFL)Cl2).

[0077] The function of the negative electrode electrolyte is to provide negative electrode active substances for the iron-based liquid flow battery. The active substances are redox pairs with redox reversibility, which are paired with the redox pairs in the positive electrode electrolyte. Reduction reactions can occur at the negative electrode during the charging process of the iron-based liquid flow battery and oxidation reactions can occur during the discharge process. Different negative electrode electrolytes are assembled with corresponding iron positive electrode electrolytes into iron-based liquid flow batteries of different systems.

[0078] Preparation of positive electrode electrolyte: Dissolve ferrocyanide or its oxidized state in water to obtain a positive electrode active material with a concentration of 0.1 M to 1.74 M, then add a delithiation catalyst and 0.1 M to 4.0 M of a positive electrode supporting electrolyte, and use a magnetic stirrer to fully stir and dissolve. The specific concentration of the positive electrode electrolyte needs to be adjusted according to the matching negative electrode electrolyte.

[0079] The function of the positive electrode electrolyte is to provide positive electrode active material for the iron-based liquid flow battery. The active material is a redox couple with redox reversibility, which is paired with the redox couple in the negative electrode electrolyte. In the iron-based liquid flow battery, an oxidation reaction occurs at the positive electrode during charging and a reduction reaction occurs during discharge.

[0080] Ferrocyanide includes: one or more of potassium ferrocyanide, sodium ferrocyanide, ammonium ferrocyanide, lithium ferrocyanide, Prussian blue, and Prussian white; the oxidation state of ferrocyanide includes one or more of potassium ferrocyanide, sodium ferrocyanide, and lithium ferrocyanide.

[0081] Selection of delithiation catalyst (0.1 M~4.0 M): vanadyl sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium perchlorate, ferrocene and its derivatives, nitrogen oxides, hydroquinone and its derivatives, one or more of the above compounds are dissolved in an aqueous solution. The working principle of the delithiation catalyst is that when the potential of the delithiation catalyst is higher than that of the waste lithium-ion battery positive electrode material, the high potential has an oxidizing effect on the low potential, and the delithiation of the waste lithium-ion battery positive electrode material can be achieved.

[0082] Among them, nitroxides include 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO), 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide (4-OH-TEMPO), 4-[3-(trimethylamino)propoxy]-2,2,6,6-tetramethylpiperidinyl-1-oxyl (TMAP-TEMPO), 4-(sodium propoxy-3-sulfonate)-2,2,6,6-tetramethylpiperidinyl-1-oxyl (PSS-TEMPO), 2,2,6,6-tetramethylpiperidinyl-N-oxyl (MIAcNH-TEMPO), N¹, N¹, N¹, N³, N³, 2,2,6,6-nonylmethyl-N³-(piperidinyloxy)propane-1,3-bis(diammonium chloride) (N2-TEMPO), cation-grafted TEMPO (Cation-grafted TEMPO, g+-TEMPO), N,N,N-2,2,6,6-heptamethylpiperidinyloxy-4-ammonium chloride (TMA-TEMPO), TEMPO-potassium sulfate, 1-(4-(((1-oxy-2,2,6,6-tetramethylpiperidin-4-yl)oxy)carbonyl)benzyl)-1′-methyl-[4,4′-bipyridine]-1,1′-dichloride (VIOTEMP), riboflavin-TEMPO (Riboflavin n-TEMPO, RIBOTEMPO), 1-(1-oxy-2,2,6,6-tetramethylpiperidin-4-yl)-1′-(3-(trimethylamino)propyl)-4,4′-bipyridinium trichloride ((TPABPy)Cl3), and cationic imidazole-grafted TEMPO, as well as 1,5-bis(2-(2-(2-(1-0-yl-2,2,6,6-tetramethylpiperidin-4-yl)oxy)ethoxy)ethoxy)benzimidazine compounds.

[0083] Among them, the structural formula of TEMPO is The structural formula of 4-OH-TEMPO is The structural formula of TMAP-TEMPO is The structural formula of PSS-TEMPO is 、MIAcNH-TEMPO structural formula is 、N2-TEMPO structural formula is 、g+-TEMPO The structural formula of TMA-TEMPO is , TEMPO-potassium sulfate salt structural formula is The structural formula of VIOTEMP is , RIBOTEMPO structural formula is The structural formula of (TPABPy)Cl3 is , cationic imidazole grafted TEMPO structural formula is The structural formula of 1,5-bis(2-(2-(2-(1-0-yl-2,2,6,6-tetramethylpiperidin-4-yl)oxy)ethoxy)ethoxyethoxy)benzimine is .

[0084] Among them, hydroquinone and its derivatives include: 4,5-dihydroxy-1,3-benzenedisulfonic acid disodium salt monohydrate (BQDS), 1,4-dihydroxybenzenesulfonic acid potassium (HQS), 3,6-dihydroxy-2,4-dimethylbenzenesulfonic acid (DHDMBS), 3-fluorocatechol (3FQH2), tetrafluorohydroquinone (TFQH2), 3,3′,5,5′-tetramethylaminomethylene-4,4′-biphenol (TABP), 2-methoxy-1,4-hydroquinone (MHQ), 2,3-Dimethyl-5-[(morpholin-4-yl)methyl]benzene-1,4-diol (MMHQ), 2,5-bis[(morpholin-4-yl)methyl]benzene-1,4-diol (DMHQ), 2,5-dimethyl-3,6-bis[(morpholin-4-yl)methyl]benzene-1,4-diol (sym-DDHQ), 2,6-dimethyl-3,5-bis[(morpholin-4-yl)methyl]benzene-1,4-diol (asym-DDHQ) and sulfonated thioethers of benzene.

[0085] Among them, the structural formula of BQDS is The structural formula of HQS is The structural formula of DHDMBS is The structural formula of 3FQH2 is The structural formula of TFQH2 is The structural formula of TABP is The structural formula of MHQ is The structural formula of MMHQ is The structural formula of DMHQ is The structural formula of sym-DDHQ is The structural formula of asym-DDHQ is The structural formula of the sulfonated sulfide substituted diphenol is .

[0086] The positive electrode supporting electrolyte is a mixture of one or more solutions of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid.

[0087] It should be noted that the selection of delithiation catalyst needs to match the positive electrode material of the waste lithium-ion battery, and the potential of the selected material needs to be higher than that of the positive electrode material of the waste lithium-ion battery. Figure 5 This is a comparison of the potentials of different waste lithium-ion battery cathode materials and delithiation catalysts, where:

[0088] The standard electrode potential of ferrocyanide and its oxidized form is approximately 0.5V.

[0089] Vanadyl sulfate forms VO 2+ / VO2 + The standard electrode potential of the electrode pair is 0.99V.

[0090] Ferric chloride, ferrous chloride, ferrous sulfate, Fe formed by ferrous sulfate 2+ / Fe 3+ The standard electrode potential of the electrode pair is 0.77V.

[0091] Potassium iodide and sodium iodide form I - / I3 - ,I - / I2、I - / I03 - The standard electrode potentials are 0.53 V, 0.53 V, and 1.08 V.

[0092] Potassium bromide and sodium bromide form Br - The standard electrode potential of / Br2 is 1.08V.

[0093] Manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate form Mn 3+ / Mn 2+ 、MnO4 - / Mn 2+ 、MnO4 - The standard electrode potentials of / MnO2 are 1.53V, 1.5V, and 1.68V.

[0094] Cerium chloride, cerium sulfate, cerium perchlorate, cerium oxyperchlorate form Ce 4+ / Ce 3+ The standard electrode potential is 1.72V.

[0095] The standard electrode potential of ferrocene and its derivatives is greater than 0.69V.

[0096] The standard electrode potential of nitrogen oxides is greater than 0.8V.

[0097] The standard electrode potential of hydroquinone and its derivatives is greater than 0.69V.

[0098] Specifically, when recycling waste lithium iron phosphate, the potential of waste lithium iron phosphate is about 0.36 V. The delithiation catalyst can be selected from one or more of vanadium ferric sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium oxychlorate, ferrocene and its derivatives, nitrogen oxides, and hydroquinone and its derivatives, and the selected materials are all greater than 0.36 V.

[0099] Specifically, when recycling waste lithium cobalt oxide, the potential of waste lithium cobalt oxide is about 0.66 V. The delithiation catalyst can be selected from one or more of ferrocyanide and its oxidation state, vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium oxyperchlorate, ferrocene and its derivatives, nitrogen oxides, and hydroquinone and its derivatives, and the potential of the selected materials is greater than 0.66 V.

[0100] Specifically, when recycling waste lithium manganate, the potential of waste lithium manganate is about 0.96 V. The delithiation catalyst can be selected from one or more of vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, and cerium oxyperchlorate, and the potential of the selected materials is greater than 0.96 V.

[0101] Specifically, when waste nickel cobalt aluminum oxide is selected for recycling, the potential of waste nickel cobalt aluminum oxide is about 0.46 V. The delithiation catalyst can be selected from one or more of vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium oxychlorate, ferrocene and its derivatives, nitrogen oxides, and hydroquinone and its derivatives, and the potential of the selected materials is greater than 0.46 V.

[0102] Specifically, when the waste nickel cobalt manganese oxide is selected for recycling, the potential of the waste nickel cobalt manganese oxide is about 0.46 V. The delithiation catalyst can be selected from one or more of vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium perchlorate, ferrocene and its derivatives, nitrogen oxides, and hydroquinone and its derivatives, and the potential of the selected materials is greater than 0.46 V.

[0103] The concentration of the positive electrode electrolyte affects the battery capacity density. When the concentration of the positive electrode electrolyte is too low, the battery capacity density is affected by the concentration. However, when the concentration of the positive electrode electrolyte is too high, the viscosity of the electrolyte increases, affecting the stability of the battery. As the concentration of the battery increases, the stability will gradually decrease. When the concentration is 0.01 M~2.0 M, the positive electrode electrolyte can provide a higher capacity and reduce the impact of excessive concentration on battery stability.

[0104] In the embodiment of the present invention, the selection of specific positive and negative supporting electrolytes needs to be determined based on the ions provided by the positive and negative active materials, which play the role of providing salt ions and balancing the ion concentrations of the positive and negative electrodes. For example: when K4Fe(CN)6 is selected as the active material for the positive electrode, K ions play a transport role, so it is necessary to use supporting electrolytes containing K ions, including KCl, KOH, K2CO3, etc. When selecting a supporting electrolyte, it is necessary not only to pay attention to the selection of the type, but also to the selection of the concentration. The molar concentration that can minimize the difference in ion concentration in the positive and negative electrode electrolytes and minimize water migration between the positive and negative electrodes is the best supporting electrolyte molar concentration.

[0105] Preparation of positive electrode materials for waste lithium-ion batteries: dismantle waste lithium-ion batteries, use a variety of solutions to remove residual electrolyte on the electrode surface, obtain battery positive electrode sheets, and then crush the obtained positive electrode materials to obtain granular solid positive electrode materials for waste lithium-ion batteries.

[0106] The function of the filter device is mainly to prevent the waste lithium-ion battery positive electrode material from entering the positive electrode half-cell or the transmission pipeline, causing the battery electrolyte transmission pipeline to be blocked and affecting the battery life. The positive electrode material of the lithium-ion battery is coated with a filter cloth and placed in the positive electrode storage tank, or porous materials such as carbon felt, carbon cloth and graphite felt are used to filter between the positive electrode storage tank and the transportation pipeline. However, the presence of the filter device cannot affect the flow rate of the electrolyte and the reaction process.

[0107] The filtering device is any one of polyester filter cloth, polypropylene filter cloth, nylon filter cloth, vinylon filter cloth, polyethersulfone filter membrane, graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphene modified carbon felt, graphyne modified carbon felt, nickel mesh, modified nickel mesh, biomass modified electrode, sulfide modified electrode, bismuth modified electrode, carbon nanotube composite electrode, and silicon oxide modified electrode.

[0108] The prepared diaphragm, positive electrolyte, negative electrolyte, positive and negative electrodes, waste lithium-ion battery positive electrode materials, and filtration device are assembled into an iron-based liquid flow battery and tested using battery testing systems such as Xinwei, Blue Electric, and Arbin.

[0109] The principle of lithium-ion-enhanced iron-based flow battery is that lithium ions are precipitated from the cathode material of waste lithium-ion batteries and enter the iron cathode solution, the solution solvation structure changes, the binding energy changes, and the stability of the iron-based electrolyte is greatly improved. The calculation formula of the binding energy is as follows:

[0110] ;

[0111] In the formula, E bonding is the solution binding energy, E toatalis the energy of the solution ion clusters, E A is the energy of ferrocyanide in the solution, E B Energy for other components.

[0112] Example 1

[0113] The Nafion 212 membrane used in this embodiment needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a 1 M NaOH alkaline solution is prepared and heated to 80°C. After the temperature is constant, the cut membrane is placed in it and heated for 1.5 h. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0114] Preparation of electrode materials: Carbon felt with a length of 4.5 cm, a width of 3.0 cm and a thickness of 5.0 mm was used as the positive and negative electrode materials of the battery.

[0115] Preparation of positive electrode electrolyte: Dissolve 0.5 M K4Fe(CN)6 and 0.5 M Na4Fe(CN)6 in 0.5 M NaOH solution. After they are completely dissolved, fill a volumetric flask with water at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0116] Preparation of negative electrode electrolyte: To ensure the dissolution of ZnBr2, it is necessary to prepare a supporting electrolyte solution first. Dissolve 4 M NaOH in water, cool to room temperature, and place 0.2 M ZnBr2 in the cooled alkaline solution. Stir until the solid is completely dissolved. After cooling to room temperature, use a volumetric flask to make up the volume. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0117] Preparation of positive electrode materials for waste lithium-ion batteries: Take 3 g of waste lithium iron phosphate, rinse it with deionized water and alcohol to remove the residual electrolyte on the electrode surface, crush it, wrap it with polyester filter cloth, and then put it into the positive electrode electrolyte until it is completely soaked.

[0118] In this embodiment, 0.5 M NaOH solution containing 3 g of waste lithium iron phosphate, 0.5 M K4Fe(CN)6 and 0.5 M Na4Fe(CN)6 was used as the positive electrolyte, 0.2 M ZnBr2 and 4 M NaOH alkaline solution was used as the negative electrolyte, carbon felt was used as the positive and negative electrode materials of the flow battery, and ionized Nafion 212 membrane was used as the diaphragm, and the key materials were assembled into a zinc-iron flow battery. The test was carried out using the Xinwei electrochemical test system.

[0119] The zinc-iron liquid flow battery of Example 1 was subjected to a constant current charge-discharge cycle performance test at room temperature, with the flow rates of the positive and negative electrolytes both being 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Figure 6 As shown, at 50 mA cm -2 At a current density of , the battery cycle was stable for 21,000 cycles, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 85.91%, and an average energy efficiency of 85.5%. The embodiment proves that after adding lithium iron phosphate as the positive electrode material of waste lithium-ion batteries, the battery stability is greatly improved at high current density.

[0120] The extraction rate of lithium ions in the cathode solution with the cycle time, the lithium content in the cathode solution was analyzed every 3 minutes using an inductively coupled plasma emission spectrometer, the data are as follows Figure 7 As shown, with the passage of time, the content of lithium in the solution continues to increase, and after 10 minutes, the extraction rate of lithium reaches 99%, which indicates that lithium ions are almost completely extracted from the positive electrode solution.

[0121] Since the potential of ferrocyanide is higher than that of lithium iron phosphate, ferrocyanide also has the effect of delithiation of lithium iron phosphate.

[0122] The zinc-iron flow battery of Example 1 was subjected to a battery rate cycle test using a Xinwei test system, and the test procedure was a rate test procedure. The charge and discharge current densities were 50 mA cm -2 , 100 mA cm -2 , 150 mA cm -2 , 200 mAcm -2 , 250 mA cm -2 , 300 mA cm -2 The battery rate performance was tested using the Xinwei test platform. The current density of the test battery was controlled by the Xinwei test software design program. The battery reaction area was known, and the device test current was controlled, which is known in the art. The flow rate of the positive and negative electrolytes was 20 mL min -1 The charge cut-off voltage is 2.1 V, the discharge cut-off voltage is 1.2 V, and the stable cycle is 70 cycles at different current densities. Fig.18 As shown, at 50 mA cm -2 At a current density of 100 mAcm, the average Coulomb efficiency is 99.5%, the average voltage efficiency is 93.3%, and the average energy efficiency is 92.9%. -2At a current density of 150 mA cm, the average Coulomb efficiency, average voltage efficiency and average energy efficiency are 99.6%, 87.4% and 87.1%, respectively. -2 At a current density of 200 mA cm, the average Coulomb efficiency, average voltage efficiency and average energy efficiency are 99.7%, 82.0% and 81.8%, respectively. -2 At a current density of 250 mA cm, the average Coulomb efficiency, average voltage efficiency and average energy efficiency are 99.6%, 78.1% and 77.8%, respectively. -2 At a current density of 300 mA cm, the average Coulomb efficiency is 99.6%, the average voltage efficiency is 74.5%, and the average energy efficiency is 74.2%. -2 At a current density of 50 mA cm, the average Coulomb efficiency is 99.3%, the average voltage efficiency is 70.7%, and the average energy efficiency is 70.2%. -2 Afterwards, its average coulombic efficiency, average voltage efficiency and average energy efficiency were close to the data of the first ten cycles, indicating that the iron-based electrolyte had high stability at different current densities after adding waste lithium iron phosphate, and the stability of the iron-based electrolyte was not affected at high current density.

[0123] Example 2

[0124] The difference from Example 1 is that the working environment temperature of the battery test is -20°C.

[0125] The zinc-iron flow battery of Example 2 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Figure 8 It can be seen that at 50 mA cm -2 Under a current density of , the battery can be stably cycled for 3000 times, with an average coulombic efficiency of 100.0%, an average voltage efficiency of 80.5%, and an average energy efficiency of 80.5%.

[0126] Example 2 proves that lithium ions can effectively improve the stability of positive electrode active materials at low temperatures, and the assembled zinc-iron flow battery can be stably cycled.

[0127] Example 3

[0128] The difference from Example 1 is that the working environment temperature of the battery test is from -20°C to 0°C, and the temperature is increased by 5°C every 100 cycles.

[0129] The zinc-iron liquid flow battery of Example 3 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig. 9 It can be seen that at 50 mA cm -2 The current density of 50 mA cm-1 was stable for 500 cycles. -2 At a current density of 1.547 W / m, at 0°C, the average coulombic efficiency of the battery was 99.8%, the average voltage efficiency was 80.1%, and the average energy efficiency was 80.0%; at -5°C, the average coulombic efficiency of the battery was 99.9%, the average voltage efficiency was 79.3%, and the average energy efficiency was 79.4%; at -10°C, the average coulombic efficiency of the battery was 99.5%, the average voltage efficiency was 77.4%, and the average energy efficiency was 77.0%; at -15°C, the average coulombic efficiency of the battery was 99.4%, the average voltage efficiency was 75.5%, and the average energy efficiency was 75.0%; at -20°C, the average coulombic efficiency of the battery was 99.9%, the average voltage efficiency was 72.5%, and the average energy efficiency was 72.4%; This shows that after adding waste lithium iron phosphate, the iron-based electrolyte has high stability under different conditions, and the stability of the iron-based electrolyte is not affected at low temperatures, which effectively verifies that the addition of lithium ions can effectively improve the adaptability of the battery to temperature changes.

[0130] Example 4

[0131] The difference from Example 1 is that the working environment temperature of the battery test is 60°C.

[0132] The zinc-iron liquid flow battery of Example 4 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.10 It can be seen that at 100 mA cm -2 Under a current density of , it can stably cycle for 8000 times, with an average coulombic efficiency of 99.99%, an average voltage efficiency of 85.5%, and an average energy efficiency of 85.5%.

[0133] Example 4 proves that lithium ions can effectively improve the stability of the positive electrode active material at low temperatures, and the assembled zinc-iron flow battery can be stably cycled.

[0134] Example 5

[0135] The difference from Example 1 is that the concentration of the positive electrode active material is changed, and the concentration of ferrocyanide is 1.74M.

[0136] In this embodiment, the positive electrode electrolyte is prepared by dissolving 0.87 M K4Fe(CN)6 and 0.87 M Na4Fe(CN)6 in a 0.5 M NaOH solution. After the solution is completely dissolved, the volume is fixed in a volumetric flask at room temperature. A certain volume of solution is taken from the volumetric flask and placed in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0137] The zinc-iron liquid flow battery of Example 5 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.11 It can be seen that at 100 mA cm -2 Under a current density of , the battery can be stably cycled for 5000 cycles, with an average coulombic efficiency of 99.4%, an average voltage efficiency of 84.3%, and an average energy efficiency of 84.8%.

[0138] Example 5 proves that lithium ions can effectively improve the solubility of positive electrode active materials and greatly improve the energy density of batteries. At the same time, the addition of lithium ions can not only improve the solubility, but also greatly improve the stability of high-concentration ferrocyanide during battery operation. Fig.12 The capacity released by 1.74 M is increased by 64.7% compared with the capacity released by 1.0 M ferrocyanide.

[0139] Increasing the concentration of ferrocyanide to 1.74 M will increase the energy density of the battery. However, the viscosity of the positive electrode solution of the battery will increase due to the increase in concentration, which will reduce the stability of the battery. Therefore, the number of cycles will be slightly lower than that of low concentration.

[0140] Example 6

[0141] The difference from Example 1 is that the type of positive electrode material of waste lithium-ion batteries is changed. In this example, lithium cobalt oxide is used as the positive electrode material of waste lithium-ion batteries. At the same time, a delithiation catalyst with a potential higher than that of lithium cobalt oxide is added. In this example, 1 M 4-OH-TEMPO is used as the delithiation catalyst.

[0142] The working electrode was a glassy carbon electrode, the counter electrode was a platinum electrode, and the reference electrode was a silver / silver chloride electrode. The scan rate was set to 50 mV s -1 The cut-off voltage was set at 0.5 V and 1.1 V, and cyclic voltammetry was performed on 4-OH-TEMPO. The data are shown in Fig.13 As shown, 4-OH-TEMPO exhibits excellent reversibility, and the redox potential of the catalyst is higher than that of lithium cobalt oxide.

[0143] Preparation of positive electrode electrolyte: Dissolve 0.5 M K4Fe(CN)6 and 0.5 M Na4Fe(CN)6 in 0.3 M NaCl solution, add 1 M TEMPO, and after complete dissolution, fill the volumetric flask at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0144] Preparation of positive electrode materials for waste lithium-ion batteries: Take 3 g of waste lithium cobalt oxide, rinse it with deionized water and alcohol to remove the residual electrolyte on the electrode surface, crush it, wrap it with polyester filter cloth, and then put it into the positive electrode electrolyte until it is completely soaked.

[0145] In this embodiment, 1 M TEMPO was used, while 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6 and 0.3 M NaCl solution containing 3 g of waste lithium cobalt oxide were used as the positive electrolyte, 0.2 M ZnBr2 and 4 M NaOH alkaline solution were used as the negative electrolyte, carbon felt was used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane was used as the diaphragm, and the key materials were assembled into a zinc-iron flow battery. The test was performed using the Xinwei electrochemical test system.

[0146] The zinc-iron liquid flow battery of Example 6 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.14 As shown, at 100 mA cm -2 At a current density of , the battery cycle was stable for 14,600 cycles, with an average coulombic efficiency of 99.4%, an average voltage efficiency of 84.3%, and an average energy efficiency of 84.8%. The embodiment proves that after adding lithium cobalt oxide as the positive electrode material of waste lithium-ion batteries, the battery stability is greatly improved at high current density.

[0147] The delithiation catalyst used in this embodiment mainly plays the role of extracting lithium. Compared with Example 1, the number of cycles is relatively low, but compared with the typical high-concentration zinc-iron flow battery without adding lithium ions, which can only cycle a few hundred times, the number of cycles is greatly improved. All embodiments of the present invention are greatly improved compared to typical iron-based flow batteries. Typical iron-based flow batteries can only cycle a few hundred times under high concentration conditions, while all embodiments of the present invention can cycle more than 1,000 times.

[0148] Example 7

[0149] The difference from Example 1 is that the type of positive electrode material of waste lithium-ion batteries is changed. In this example, lithium manganese oxide is used as the positive electrode material of waste lithium-ion batteries. At the same time, a delithiation catalyst with a higher potential than lithium manganese oxide is added. In this example, 1 M KBr is used as the delithiation catalyst.

[0150] Preparation of positive electrode materials for waste lithium-ion batteries: Take 3 g of waste lithium manganese oxide, rinse it with deionized water and alcohol to remove the residual electrolyte on the electrode surface, crush it, wrap it with polyester filter cloth, and then put it into the positive electrode electrolyte until it is completely soaked.

[0151] In this embodiment, 1 M KBr was added, 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6, 0.3 M NaCl solution containing 3 g of waste lithium manganese oxide was used as the positive electrolyte, 0.2 M ZnBr2 and 4 M NaOH alkaline solution were used as the negative electrolyte, carbon felt was used as the positive and negative electrode materials of the flow battery, and ionized Nafion 212 membrane was used as the diaphragm, and the key materials were assembled into a zinc-iron flow battery. The test was carried out using the Xinwei electrochemical test system.

[0152] The zinc-iron flow battery of Example 7 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.15 As shown, at 100 mA cm -2 At a current density of , the battery cycle was stable for 11,000 cycles, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 82.0%, and an average energy efficiency of 82.4%. The embodiment proves that after adding lithium manganese oxide, the battery stability is greatly improved at high current density.

[0153] Example 8

[0154] The difference from Example 1 is that the type of positive electrode material of waste lithium-ion batteries is changed. In this example, lithium nickel cobalt manganese oxide is used as the positive electrode material of waste lithium-ion batteries. At the same time, a delithiation catalyst with a potential higher than that of lithium cobalt oxide is added. In this example, 1 M 4-OH-TEMPO is used as the delithiation catalyst.

[0155] Preparation of positive electrode materials for waste lithium-ion batteries: Take 3 g of waste lithium nickel cobalt manganese oxide, rinse it with deionized water and alcohol to remove the residual electrolyte on the electrode surface, crush it, wrap it with polyester filter cloth, and then put it into the positive electrode electrolyte until it is completely soaked.

[0156] In this embodiment, 1 M 4-OH-TEMPO was added, 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6, 0.3 M NaCl alkaline solution containing 3 g of waste nickel cobalt manganese oxide was used as the positive electrolyte, 0.2 M ZnBr2 4 MNaOH alkaline solution was used as the negative electrolyte, carbon felt was used as the positive and negative electrode materials of the flow battery, and ionized Nafion212 membrane was used as the diaphragm, and the key materials were assembled into a zinc-iron flow battery. The test was performed using the Xinwei electrochemical test system.

[0157] The zinc-iron flow battery of Example 8 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.16 As shown, at 100 mA cm -2 At a current density of , the battery cycle was stable for 1800 cycles, with an average coulombic efficiency of 98.5%, an average voltage efficiency of 83.3%, and an average energy efficiency of 82.0%. The embodiment proves that after adding lithium nickel cobalt manganese oxide, the battery stability is greatly improved at high current density.

[0158] The waste lithium-ion positive electrode recovered in this embodiment is a ternary lithium positive electrode material, which is more unstable in the air than lithium iron phosphate. Therefore, the lithium element recovered from the failed ternary lithium positive electrode is limited, and the improvement of the positive electrode is limited, resulting in a lower number of battery cycles than in Example 1, but it can still be greatly improved compared to typical iron-based liquid flow batteries.

[0159] Example 9

[0160] The difference from Example 1 is that the type of positive electrode material of waste lithium-ion batteries is changed. In this example, nickel cobalt aluminum oxide is used as the positive electrode material of waste lithium-ion batteries. At the same time, a delithiation catalyst with a potential higher than that of nickel cobalt aluminum oxide is added. In this example, 1 M 4-OH-TEMPO is used as the delithiation catalyst.

[0161] Preparation of positive electrode materials for waste lithium-ion batteries: Take 3 g of waste nickel cobalt aluminum oxide, rinse it with deionized water and alcohol to remove the residual electrolyte on the electrode surface, crush it, wrap it with polyester filter cloth, and then put it into the positive electrode electrolyte until it is completely soaked.

[0162] In this embodiment, 1 M 4-OH-TEMPO was added, 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6, 0.3 M NaCl solution containing 3 g of waste lithium nickel cobalt aluminum oxide was used as the positive electrolyte, 0.2 M ZnBr2 4 MNaOH alkaline solution was used as the negative electrolyte, carbon felt was used as the positive and negative electrode materials of the flow battery, and ionized Nafion212 membrane was used as the diaphragm, and the key materials were assembled into a zinc-iron flow battery. The test was performed using the Xinwei electrochemical test system.

[0163] The zinc-iron flow battery of Example 9 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.17 As shown, at 100 mA cm -2 At a current density of , the battery cycle was stable for 3400 cycles, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 86.9%, and an average energy efficiency of 86.5%. The embodiment proves that after adding lithium nickel cobalt aluminum oxide, the battery stability is greatly improved at high current density.

[0164] The present invention can verify that the recycled lithium element has an improvement effect on the iron-based electrolyte in the flow battery by changing different types of waste lithium-ion battery positive electrode materials. This means that recycling lithium elements from different types of lithium-ion battery positive electrode materials can improve the stability of iron-based flow batteries, and the wide selectivity of waste lithium ion types further promotes the commercial application of the present invention.

[0165] Example 10

[0166] The difference from Example 1 is that the Nafion 212 membrane used in this example needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a KOH alkaline solution with a concentration of 1 M is prepared and heated to 80°C. After the temperature is constant, the cut membrane is placed in it and heated for 1.5 h. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0167] Preparation of electrode materials: A carbon felt with a length of 4.5 cm, a width of 3.0 cm, and a thickness of 5.0 mm was used as the positive electrode material of the battery, and a copper sulfide-modified electrode with a length of 4.5 cm, a width of 3.0 cm, and a thickness of 5.0 mm was used as the negative electrode material of the battery. The copper sulfide-modified electrode effectively increases the conductivity of the electrode while effectively loading sulfide on the original carbon felt, which can effectively increase the reactive sites of polysulfide ions and ultimately accelerate the reaction rate of the active substance.

[0168] Preparation of negative electrode electrolyte: Dissolve 0.5 M KOH in deionized water, cool to room temperature, add 1 M K2S, stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0169] In this embodiment, 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6, and 0.3 M KOH alkaline solution containing 3 g of waste lithium iron phosphate are used as the positive electrode electrolyte, the negative electrode active material is 1.0 M K2S and 0.5 M KOH alkaline solution as the negative electrode electrolyte, carbon felt is used as the positive electrode material of the liquid flow battery, and copper sulfide modified carbon felt is used as the negative electrode material of the liquid flow battery. The ionized Nafion 212 membrane is used as the diaphragm, and the key materials are assembled into an iron-sulfur liquid flow battery. The test is carried out using the Xinwei electrochemical test system.

[0170] The constant current charge-discharge cycle performance test of the iron-sulfur liquid flow battery of Example 10 was carried out, and the flow rate of the positive electrode electrolyte and the negative electrode electrolyte was 20 mL min -1 , the charge cut-off voltage is 1.2 V, and the discharge cut-off voltage is 0.6 V. Fig.19 As shown, at 40 mA cm -2 At a current density of , it can stably cycle 3100 times, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 78.4%, and an average energy efficiency of 78.0%. This embodiment constructs an iron-sulfur liquid flow battery based on lithium elements extracted from the positive electrode of waste lithium-ion batteries, changes the type of negative electrode, and constructs different types of iron-based liquid flow batteries. After adding waste lithium iron phosphate, it has extremely high stability.

[0171] Embodiment 11

[0172] The difference from Example 1 is that the positive electrode electrolyte is prepared by dissolving 0.2 M Na4Fe(CN)6 and 0.2 M Na3Fe(CN)6 in a 3 M NaOH alkaline solution. After they are completely dissolved, the volume is fixed in a volumetric flask at room temperature. A certain volume of solution is taken from the volumetric flask and placed in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0173] Preparation of negative electrode electrolyte: Dissolve 3 M NaOH in deionized water, cool to room temperature, add 0.2 M FeCl2, 0.2 M FeCl3 and 2 M TEOA, stir until the solid is completely dissolved, cool to room temperature and use a volumetric flask to make up the volume. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0174] In this embodiment, 0.2M Na4Fe(CN)6, 0.2M Na3Fe(CN)6, 3M NaOH alkaline solution containing 3g of waste lithium iron phosphate is used as the positive electrode electrolyte, the negative electrode active material is 0.2M FeCl2, 0.2M FeCl3 and 2M TEOA, 3M NaOH alkaline solution is used as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the liquid flow battery, and the ionized Nafion212 membrane is used as the diaphragm, and the key materials are assembled into an iron-iron liquid flow battery. The test was carried out using the Xinwei electrochemical test system.

[0175] The constant current charge-discharge cycle performance test of the iron-iron liquid flow battery of Example 11 was carried out, and the flow rate of the positive electrode electrolyte and the negative electrode electrolyte was 20 mL min -1 , the charge cut-off voltage is 1.6 V, and the discharge cut-off voltage is 0.5 V. Fig. 20 As shown, at 50 mA cm -2 Under a current density of , it can stably cycle for 9000 times, with an average coulombic efficiency of 94.8%, an average voltage efficiency of 86.8%, and an average energy efficiency of 82.3%.

[0176] Example 12

[0177] The difference from Example 1 is that the Nafion 212 membrane used in this example needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a 1 M HCl acid solution is prepared at the same time. After the temperature is constant, the cut membrane is placed in it and soaked for 12 h. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0178] Preparation of positive electrode electrolyte: Dissolve 0.5M K4Fe(CN)6 and 0.5M Na3Fe(CN)6 in 1M NaOH alkaline solution. After they are completely dissolved, fill a volumetric flask with water at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0179] Preparation of negative electrode electrolyte: Dissolve 1M H2SO4 in deionized water, cool to room temperature, add 0.2M TiOSO4, stir until the solid is completely dissolved, and use a volumetric flask to make up the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0180] In this embodiment, 0.5M K4Fe(CN)6 and 0.5M Na3Fe(CN)6 containing 3g of waste lithium iron phosphate dissolved in 1M NaOH alkaline solution are used as the positive electrode electrolyte, the negative electrode active material is 0.2M TiOSO4 and 1M H2SO4 acid solution as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane is used as the diaphragm, and the key materials are assembled into an iron-titanium flow battery. The test was carried out using the Xinwei electrochemical test system.

[0181] The constant current charge-discharge cycle performance test of the iron-titanium liquid flow battery of Example 12 was carried out, and the flow rate of the positive electrode electrolyte and the negative electrode electrolyte was 20 mL min -1 , the charge cut-off voltage is 1.2 V, and the discharge cut-off voltage is 0 V. Fig.21 As shown, at 50 mA cm -2 Under a current density of , it can stably cycle for 8000 times, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 78.0%, and an average energy efficiency of 77.4%.

[0182] Embodiment 13

[0183] The difference from Example 1 is that the Nafion 117 membrane used in this example needs to be pretreated: the membrane is cut to 7.5 cm in length and 5.0 cm in width, and a 1 M HCl acid solution is prepared at the same time. After the temperature is constant, the cut membrane is placed in it and soaked for 12 hours. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0184] Preparation of positive electrode electrolyte: Dissolve 0.5 M K4Fe(CN)6 and 0.5 M Na3Fe(CN)6 in 1 M NaOH alkaline solution. After complete dissolution, fill a volumetric flask with water at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0185] Preparation of negative electrode electrolyte: Dissolve 1 M HCl in deionized water, cool to room temperature, add 0.2 M VOSO4, stir until the solid is completely dissolved, and use a volumetric flask to make up the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0186] In this embodiment, 0.5M K4Fe(CN)6 and 0.5M Na3Fe(CN)6 containing 3g of waste lithium iron phosphate dissolved in 1M NaOH alkaline solution are used as the positive electrode electrolyte, the negative electrode active material is 0.2M VOSO4 and 1M HCl acid solution as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 117 membrane is used as the diaphragm, and the key materials are assembled into an iron-vanadium flow battery. The test was carried out using the Xinwei electrochemical test system.

[0187] The constant current charge-discharge cycle performance test of the iron-vanadium liquid flow battery of Example 13 was carried out, and the flow rate of the positive electrode electrolyte and the negative electrode electrolyte was 20 mL min -1 , the charge cut-off voltage is 1.3 V, and the discharge cut-off voltage is 0.5 V. Fig. 22 As shown, at 50 mA cm -2 At a current density of , the battery can be stably cycled for 12,000 cycles, with an average coulombic efficiency of 95.0%, an average voltage efficiency of 81.2%, and an average energy efficiency of 77.0%.

[0188] Embodiment 14

[0189] The difference from Example 1 is that the Nafion 212 membrane used in this example needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a KOH alkaline solution with a concentration of 1 M is prepared and heated to 80°C. After the temperature is constant, the cut membrane is placed in it and heated for 1.5 h. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0190] Preparation of positive electrode electrolyte: Dissolve 0.5 M K4Fe(CN)6 and 0.5 M K3Fe(CN)6 in 1 M KOH alkaline solution. After complete dissolution, fill a volumetric flask with water at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0191] Preparation of negative electrode electrolyte: Dissolve 5 M KOH in deionized water, cool to room temperature, add 0.01 M 2,6-DHAQ (2,6-dihydroxyanthraquinone), stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0192] In this embodiment, 0.3M K4Fe(CN)6, 0.3M K3Fe(CN)6, and 1M KOH alkaline solution containing 3 g of waste lithium iron phosphate are used as the positive electrode electrolyte, 0.01M 2,6-DHAQ and 5M KOH alkaline solution are used as the negative electrode electrolyte for the negative electrode active material, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane is used as the diaphragm, and the key materials are assembled into an iron-organic quinone flow battery. The test was carried out using the Xinwei electrochemical test system.

[0193] The zinc-iron flow battery of Example 14 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 1.7 V, and the discharge cut-off voltage is 0.6 V. Fig.23 As shown, at 50 mA cm -2 At a current density of , it cycled stably for 7417 times, with an average coulombic efficiency of 99.7%, an average voltage efficiency of 83.7%, and an average energy efficiency of 83.5%.

[0194] Embodiment 15

[0195] The difference from Example 1 is that the positive electrode electrolyte is prepared by dissolving 0.5 M K4Fe(CN)6 and 0.5 M K3Fe(CN)6 in 1 M NaOH alkaline solution. After they are completely dissolved, the volume is fixed in a volumetric flask at room temperature. A certain volume of solution is taken from the volumetric flask and placed in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0196] Preparation of negative electrode electrolyte: Dissolve 1 M NaOH in deionized water, cool to room temperature, add 0.1 M DHPS, stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0197] In this embodiment, 1 M NaOH alkaline solution containing 3 g of waste lithium iron phosphate, 0.5 M K4Fe(CN)6 and 0.5 M K3Fe(CN)6 was used as the positive electrode electrolyte, and 1 M NaOH alkaline solution containing 0.1 M DHPS as the negative electrode active material was used as the negative electrode electrolyte. Carbon felt was used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane was used as the diaphragm. The key materials were assembled into an iron-organic phenazine flow battery. The test was performed using the Xinwei electrochemical test system.

[0198] The constant current charge-discharge cycle performance test of the iron-organic phenazine flow battery of Example 15 was carried out, and the flow rates of the positive electrode electrolyte and the negative electrode electrolyte were both 20 mL min-1 , the charge cut-off voltage is 1.8 V, and the discharge cut-off voltage is 0.8 V. Fig.24 As shown, at 50 mA cm -2 Under a current density of , it can stably cycle 5700 times, with an average Coulomb efficiency of 99.7%, an average voltage efficiency of 77.7%, and an average energy efficiency of 77.5%.

[0199] Example 16

[0200] The difference from Example 1 is that the AEM anion membrane used in this example needs to be pre-treated: the diaphragm is cut to a length of 7.5 cm and a width of 5.0 cm, and a NaCl salt solution with a concentration of 1 M is prepared and the cut diaphragm is placed in it for use.

[0201] Preparation of positive electrode electrolyte: Dissolve 0.5 M K4Fe(CN)6 and 0.5 M Na3Fe(CN)6 in 1 M NaOH alkaline solution. After complete dissolution, fill a volumetric flask with water at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0202] Preparation of negative electrode electrolyte: Dissolve 1.5 M NaCl salt in deionized water, add 0.1 M MV, stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0203] In this embodiment, 0.5 M K4Fe(CN)6 and 0.5 M Na3Fe(CN)6 containing 3 g of waste lithium iron phosphate dissolved in 1 M NaOH alkaline solution are used as the positive electrode electrolyte, the negative electrode active material is 0.1 M MV and 1.5 M NaCl salt solution as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized AEM membrane is used as the diaphragm, and the key materials are assembled into a zinc-iron flow battery. The test was carried out using the Xinwei electrochemical test system.

[0204] The constant current charge-discharge cycle performance test of the iron-organic viologen flow battery of Example 16 was carried out, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 1.7 V, and the discharge cut-off voltage is 0.5 V. Fig.25 As shown, at 50 mA cm -2 At a current density of , it cycled stably for 8988 times, with an average coulombic efficiency of 99.5%, an average voltage efficiency of 84.9%, and an average energy efficiency of 84.5%.

[0205] Embodiment 17

[0206] The difference from Example 1 is that the Nafion 212 membrane used in this example needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a 1 M NaOH alkaline solution is prepared and heated to 25°C. After the temperature is constant, the cut membrane is placed in it and heated for 8 h. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0207] Preparation of positive electrode electrolyte: Take 0.5 M Na4Fe(CN)6 and 0.5 M Na3Fe(CN)6 and dissolve them in 1 M NaOH alkaline solution. After they are completely dissolved, fill the volume with a volumetric flask at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0208] Preparation of negative electrode electrolyte: Dissolve 1 M NaOH in deionized water, cool to room temperature, add 1 M 4C7SFL, stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0209] In this embodiment, 0.5 M Na4Fe(CN)6, 0.5 M Na3Fe(CN)6, and 1 M NaOH alkaline solution containing 3 g of waste lithium iron phosphate are used as the positive electrode electrolyte, the negative electrode active material is 0.1 M 4C7SFL and 1 M NaOH alkaline solution as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane is used as the diaphragm. The key materials are assembled into an iron-organic fluorenone flow battery. The test was carried out using the Xinwei electrochemical test system.

[0210] The constant current charge-discharge cycle performance test of the iron-organic fluorenone flow battery of Example 17 was carried out, and the flow rate of the positive electrode electrolyte and the negative electrode electrolyte was 20 mL min -1 , the charge cut-off voltage is 1.8 V, and the discharge cut-off voltage is 0 V. Fig.26 As shown, at 100 mA cm -2 At a current density of , it cycled stably for 4737 times, with an average coulombic efficiency of 99.7%, an average voltage efficiency of 76.7%, and an average energy efficiency of 76.5%.

[0211] Embodiment 18

[0212] The difference from Example 1 is that the Nafion 212 membrane used in this example needs to be pretreated: the membrane is cut to a length of 7.5 cm and a width of 5.0 cm, and a KOH alkaline solution with a concentration of 1 M is prepared and heated to 80°C. After the temperature is constant, the cut membrane is placed in it and heated for 8 hours. The membrane is then taken out, rinsed with deionized water, and placed in a beaker filled with deionized water for later use.

[0213] Preparation of positive electrode electrolyte: Take 0.5 M K4Fe(CN)6 and 0.5 M Na3Fe(CN)6 and dissolve them in 1 M KOH alkaline solution. After they are completely dissolved, fill the volume with a volumetric flask at room temperature. Take a certain volume of solution from the volumetric flask and place it in the positive electrode storage tank as the positive electrode electrolyte of the battery.

[0214] Preparation of negative electrode electrolyte: Dissolve 1 M KOH in deionized water, cool to room temperature, add 0.06 M FMN-Na, stir until the solid is completely dissolved, and use a volumetric flask to adjust the volume after cooling to room temperature. Take a certain volume of solution from the volumetric flask and place it in the negative electrode storage tank as the negative electrode electrolyte of the battery.

[0215] In this embodiment, 0.5 M K4Fe(CN)6, 0.5 M Na3Fe(CN)6 and 1 M KOH alkaline solution containing 3 g of waste lithium iron phosphate are used as the positive electrode electrolyte, the negative electrode active material is 0.1 M FMN-Na, 1 M KOH alkaline solution as the negative electrode electrolyte, carbon felt is used as the positive and negative electrode materials of the flow battery, and the ionized Nafion 212 membrane is used as the diaphragm. The key materials are assembled into an iron-organo-alloxazine flow battery. The test was performed using the Xinwei electrochemical test system.

[0216] The constant current charge-discharge cycle performance test of the iron-organic alloxazine flow battery of Example 18 was carried out, and the flow rates of the positive electrode electrolyte and the negative electrode electrolyte were both 20 mL min -1 , the charge cut-off voltage is 2 V, and the discharge cut-off voltage is 0.5 V. Fig. 27 As shown, at 20 mA cm -2 At a current density of , it can stably cycle 6600 times, with an average coulombic efficiency of 98.7%, an average voltage efficiency of 85.6%, and an average energy efficiency of 84.5%.

[0217] In the embodiment, the negative electrode is changed, and different types of iron-based flow batteries are constructed with iron-based electrolytes, including iron-organic quinone flow batteries, iron-organic phenazine flow batteries, iron-organic viologen flow batteries, iron-organic fluorenone flow batteries, and iron-organic alloxazine flow batteries. The stability of different iron-organic flow batteries is greatly improved after adding waste lithium-ion battery positive electrode materials, which effectively illustrates that the addition of waste lithium-ion battery positive electrode materials has an improvement effect on iron-based flow batteries of organic systems.

[0218] Comparative Example 1

[0219] The difference from Example 1 is that this comparative example does not add waste lithium-ion battery positive electrode materials and their matching delithiation catalysts, uses 0.5 M K4Fe(CN)6, 0.5 M Na4Fe(CN)6, and 0.3 M NaOH alkaline solution as positive electrode electrolyte, 0.2 M ZnBr2, 4 M NaOH alkaline solution as negative electrode electrolyte, uses carbon felt as positive and negative electrode materials of liquid flow battery, uses ionized Nafion 212 membrane as diaphragm, and assembles key materials into zinc-iron liquid flow battery. The test was carried out using the Xinwei electrochemical test system.

[0220] The zinc-iron liquid flow battery of comparative example 1 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.28 As shown, at 100 mA cm -2 At a current density of , the average coulombic efficiency is 98.4%, the average voltage efficiency is 79.3%, and the average energy efficiency is 78.1%. Comparative Example 1 proves that without adding waste lithium-ion battery positive electrode materials, its cycle performance decreases, and the cycle stability decreases. After 50 cycles, the stability decreases significantly. Compared with Example 1, it is found that after adding waste lithium iron phosphate battery positive electrode materials, the cycle stability of the battery is greatly improved, which effectively proves that after adding waste lithium-ion battery positive electrode materials, lithium is complexed with active substances, which improves the stability of iron-based flow batteries under high positive electrode concentration.

[0221] Comparative Example 2

[0222] The difference from Example 1 is that only 0.5 g of waste lithium iron phosphate solid is added in this comparative example.

[0223] The zinc-iron liquid flow battery of comparative example 2 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1, the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.29 As shown, at 100 mA cm -2 At a current density of , it can stably cycle for 200 cycles, with an average coulombic efficiency of 97.2%, an average voltage efficiency of 77.2%, and an average energy efficiency of 79.4%. Comparative Example 2 proves that adding a small amount of waste lithium-ion battery positive electrode material cannot effectively improve the stability of the positive electrode solution, and the cycle performance of the assembled battery decreases, and the stability decreases significantly after 200 cycles. Compared with Example 1, it is found that after adding 3g of waste lithium iron phosphate battery positive electrode material, the cycle stability of the battery is greatly improved, while only 0.5g of a small amount of waste lithium iron phosphate is added in Comparative Example 3, and the cycle performance decreases, which effectively verifies that the addition of high-quality waste lithium iron phosphate can remove lithium ions at a sufficient concentration, thereby complexing with the positive electrode and effectively improving the stability of the positive electrode solution.

[0224] Comparative Example 3

[0225] The difference from Example 1 is that this comparative example does not add waste lithium-ion battery positive electrode materials and their matching delithiation catalysts, and the test environment temperature is -20 ° C, and the test current density is only 20 mA cm -2 .

[0226] The zinc-iron liquid flow battery of comparative example 3 was subjected to a constant current charge-discharge cycle performance test, and the flow rates of the positive and negative electrolytes were both 20 mL min -1 , the charge cut-off voltage is 2.1 V, and the discharge cut-off voltage is 1.2 V. Fig.30 As shown, at 20 mA cm -2 At a current density of 10000, the coulombic efficiency, energy efficiency and voltage efficiency fluctuated greatly after only 10 stable cycles. At the same time, the capacity retention rate of the test decayed rapidly as the temperature decreased. Fig.31 As shown, the zinc-iron liquid flow battery constructed with the positive electrode solution without adding the waste lithium-ion battery positive electrode material showed crystallization in a low temperature environment, causing the battery to fail and unable to work normally. The effective comparison verified that the addition of waste lithium-ion positive electrode materials can not only effectively improve the stability of the battery, but also the iron-based liquid flow battery constructed therefrom can have good stability at low temperatures without crystallization.

[0227] The difference between Example 19 to Example 57 and Example 1 is that the waste lithium ion battery positive electrode material and the matching lithium removal catalyst added to the positive electrode electrolyte are changed. The specific components of Example 19 to Example 57 and the lithium extraction rate of the liquid flow battery composed thereof are shown in Table 1. It can be seen from Table 1 that due to the difference between the lithium removal catalyst and the waste lithium ion battery positive electrode material, the lithium extraction rate is also very different, and the difference in lithium extraction rate is caused by many reasons. First, the potential difference between the lithium extraction catalyst and the waste lithium ion battery positive electrode material will cause the difference in lithium extraction rate; secondly, the solubility, concentration, redox reversibility, etc. of the lithium extraction catalyst itself will affect the lithium extraction rate; in addition, the same and different types of waste lithium ion battery positive electrode materials are not uniform, such as lithium ion content, impurities in the positive electrode material, etc.

[0228] Table 1 Lithium extraction rate under different conditions

[0229] ;

[0230] .

[0231] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A flow battery based on recycling lithium ions to stabilize a high-concentration iron electrolyte, comprising a positive electrode storage tank and a negative electrode storage tank, characterized in that: The positive electrode storage tank stores a positive electrode electrolyte, in which a de-lithiation catalyst, a waste lithium-ion battery positive electrode material and a filter device are stored; the negative electrode storage tank stores a negative electrode electrolyte; It also includes a positive electrode half-cell and a negative electrode half-cell, and the positive electrode half-cell and the negative electrode half-cell are separated by a diaphragm; the positive electrode liquid storage tank and the positive electrode half-cell are circulated and connected through a transmission pipeline, and the negative electrode liquid storage tank and the negative electrode half-cell are circulated and connected through another transmission pipeline; and a circulation pump is provided on both transmission pipelines; The preparation method of the positive electrode electrolyte comprises: dissolving ferrocyanide or an oxidized state of ferrocyanide in water to obtain a positive electrode active substance, adding a delithiation catalyst and a positive electrode supporting electrolyte, and fully stirring and dissolving to obtain a positive electrode electrolyte; The preparation method of the delithiation catalyst comprises: dissolving one or more of vanadium sulfate, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, potassium iodide, sodium iodide, potassium bromide, sodium bromide, manganese chloride, manganese trichloride, potassium permanganate, sodium permanganate, cerium chloride, cerium sulfate, cerium perchlorate, cerium oxychlorate, ferrocene and ferrocene derivatives, nitrogen oxides, hydroquinone and hydroquinone derivatives in an aqueous solution to prepare a delithiation catalyst; the material potential of the delithiation catalyst is higher than that of the positive electrode material of the waste lithium ion battery; The concentration of the positive electrode active material is 0.1~1.74M; the concentration of the delithiation catalyst is 0.1~4.0M; the concentration of the positive electrode supporting electrolyte is 0.1~4.0M; The cathode material of the waste lithium-ion battery is lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide; Preparation of positive electrode materials for waste lithium-ion batteries: dismantle waste lithium-ion batteries, use a variety of solutions to remove residual electrolyte on the electrode surface, obtain battery positive electrode sheets, and then crush the obtained positive electrode materials to obtain granular solid positive electrode materials for waste lithium-ion batteries; Liquid flow batteries can operate normally at -20℃ to 60℃.

2. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The ferrocyanide includes one or more of potassium ferrocyanide, sodium ferrocyanide, ammonium ferrocyanide, lithium ferrocyanide, Prussian blue, and Prussian white; the oxidation state of the ferrocyanide includes one or more of potassium ferrocyanide, sodium ferrocyanide, and lithium ferrocyanide.

3. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The positive electrode supporting electrolyte is a mixture of one or more solutions of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid.

4. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The filtering device is any one of polyester filter cloth, polypropylene filter cloth, nylon filter cloth, vinylon filter cloth, polyethersulfone filter membrane, graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphene-modified carbon felt, graphyne-modified carbon felt, nickel mesh, modified nickel mesh, biomass-modified electrode, sulfide-modified electrode, bismuth-modified electrode, carbon nanotube composite electrode, and silicon oxide-modified electrode; the filtering device is used to prevent waste lithium-ion battery positive electrode materials from entering the positive electrode half-cell or transmission pipeline.

5. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The preparation method of the diaphragm is as follows: When using K + 、Na + , Li + or NH4 + When ions are used as positive and negative electrode conducting ions, the diaphragm is placed in an alkaline solution having corresponding positive and negative electrode conducting ions selected from the group consisting of LiOH, NaOH, KOH, NH3·H2O, NH4 HCO3, (NH4)2CO3, Li2CO3, Li2HCO3, Na2CO3, NaHCO3, K2CO3, KHCO3, Li2O, Na2O or K2O, and the diaphragm is subjected to constant temperature treatment at a temperature of 25°C to 80°C for 1.5h to 12h. After the constant temperature heating treatment, the diaphragm is repeatedly washed with deionized water until the pH value of the deionized water is 6 to 7, and K + 、Na + , Li + or NH4 + Type ion exchange membrane; When using H + When used as positive and negative electrode ion conductors, the diaphragm is treated with hydrochloric acid or sulfuric acid before use to fill the diaphragm with H + , the membrane was repeatedly washed with deionized water until the pH of the deionized water was 6-7, and H + Type ion exchange membrane; When anions are used as positive and negative electrode conductive ions, the diaphragm is soaked in a supporting electrolyte or a solution prepared with positive and negative electrode active materials before use, and then treated at a constant temperature. The diaphragm is then repeatedly washed with deionized water until the pH of the deionized water is 6~7, thereby obtaining an anionic ion exchange membrane.

6. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The electrode of the positive half-cell and the electrode of the negative half-cell both use any one of graphite felt, carbon felt, carbon paper, carbon cloth, carbon plate, nickel mesh, graphite plate, graphene-modified carbon felt, graphyne-modified carbon felt, nickel mesh, modified nickel mesh, activated carbon, carbon nanotubes, carbon aerogel, biomass-modified electrode, sulfide-modified electrode, bismuth-modified electrode, carbon nanotube composite electrode, and silicon oxide-modified electrode as the electrode material.

7. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 1, characterized in that: The preparation method of the negative electrode electrolyte is: One or more of zinc-containing compounds, sulfides, iron-containing compounds, titanium-containing compounds, vanadium-containing compounds, quinone derivatives, phenazine derivatives, viologen derivatives, alloxazine derivatives, and fluorenone derivatives are dissolved in an aqueous solution, and then a negative electrode supporting electrolyte is added and fully stirred to dissolve.

8. The flow battery based on recycling lithium ions to stabilize high-concentration iron electrolyte according to claim 7, characterized in that: The negative electrode supporting electrolyte is any one of alkali, lithium salt, sodium salt, potassium salt, calcium salt, ammonium salt, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, or a mixture of multiple solutions.

Citation Information

Patent Citations

  • Method for obtaining ultrapure iron phosphate from waste lithium iron phosphate pole piece material, and obtained ultrapure iron phosphate

    CN114084877A

  • Electrochemical energy storage research method

    CN111933985A

  • Preparation method of material or metal elementary substance capable of being embedded with alkali metal ions

    CN112018370A

  • A lithium ion battery material recycling method

    CN112996931A

  • Electrochemistry-based waste lithium iron phosphate repairing and recycling method

    CN113086961A